4CPS-030 Incidence and risk factors for prosthetic joint infection within 90 days after hemiarthroplasty for femoral neck fractures in the elderly. (24th March 2020) - Declercq, P; Vanden Broeck, L; Moons, L; Du Bois, I; Scherrenberg, D; Spriet, I; Sermon, A; Metsemakers, WJ
Abstract : Background and importance: Closed femoral neck fractures after low impact trauma in the elderly are often treated with hemiarthroplasty. In this setting, the literature with respect to prosthetic joint infection (PJI) is scarce. Aim and objectives: The objectives of this study were to investigate the incidence of PJI and the impact of the number of perioperative antimicrobial prophylaxis (PAP) administrations. Furthermore, in this population, risk factors for PJI were identified. Material and methods: In this retrospective monocentric study, medical files of elderly (≥75 years) trauma patients with closed femoral neck fractures and treated with a hemiarthroplasty, admitted between January 2006 and July 2017, were evaluated. Patient follow-up was 90 days. A Cox proportional hazards regression analysis with forward step was applied. Results were considered statistically significant if p<0.05. Results: A consecutive series of 745 patients (mean age 85±5 years, 221 (29.7%) men) were treated with a hemiarthroplasty. Within 90 postoperative days, 13 (1.7%) patients developed a PJI and 120 (16.1%) died due to reasons other than infection. The applied PAP regimens consisted of intravenous cefazoline or clindamycin. Single and repeated PAP administrations (every 8 hours) were observed. Patients who developed a PJI received a median of 1 (IQR 1–2) PAP administration, which was not significantly different compared with PAP administrations in patients that did not develop a PJI (1 (IQR 1–3)) (HR=0.236 (95% CI 0.032 – 1.745); p=0.157). Higher body weight (HR=1.05 (95% CI 1.008–1.094); p=0.020), systemic corticoid use (HR=4.790 (95% CI 1.275–17.997; p=0.020) and the need for transfer to the intensive care unit (ICU) for reasons other than infection (HR=8.692 (95% CI 2.353–32.106; p=0.001) were independently associated with the development of a PJI within 90 days. Conclusion and relevance: In this fragile trauma population, the observed 1.7% PJI incidence within 90 days was low compared with the incidence rate of 3.4–4.5% in the literature. Our preliminary data showed that the number of PAP administrations did not influence the risk of PJI. Patients with a higher body weight, with systemic corticoid use or with postoperative ICU transfer should be monitored closely for infection. References and/or acknowledgements: No conflict of interest.